THE IMPACT OF LUMBAR SPINE DISEASE ON HIP-SPINE RELATIONSHIP IN TOTAL HIP ARTHROPLASTY: A SYSTEMATIC REVIEW - Gunawan, Indra (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Since 1983, when the hip-spine condition was proposed for the first time, a substantial amount of research has been conducted on the hip-spine connection. Tilt-related lumbar spine disease, commonly known as LSD, has been the focus of much research and is now recognized as an independent risk factor for dislocation, which can lead to an increased likelihood of revision total hip arthroplasty (THA). Due to the inflexible sacroiliac attachments, normal spinopelvic motion consists of the pelvis tilting backwards in a seated posture and forwards in a standing position. In addition, the common lumbar illnesses, such as degenerative disc disease (DDD), degenerative lumbar spondylolisthesis (DSPL), ankylosing spondylitis (AS), and lumbar spinal fusion (LSF), have various spinal-hip-femoral compensatory processes. Even with the appropriate placement of the prosthesis, these mechanisms can contribute to intraoperative complications, such as difficulty in hip implantation and the potential for hip repositioning. For the evaluation of spinopelvic mobility, LSD is a significant element. To achieve a satisfying THA with a low rate of dislocation and wear, the surgeon should pay closer attention to the correlation between lumbar disease and sagittal spinal balance, and then develop treatment strategies based on the patients' risk classifications.